PERAN BUDAYA BOBATU DALAM PENGELOLAAN SUMBERDAYA KELAUTAN DI DISTRIK DEMTA, JAYAPURA, PAPUA - Wally, Yusuf (Sabda: Jurnal Kajian Kebudayaan, 2011)
This paper discusses the values of local wisdom Bobatu and its role in adaptive management of marine resources in the District of Demta. A problem in this connection includes the management of marine resources applied in Indonesia and the centralized nature of the alleged to be one factor affecting the depletion of coastal resources. Supervision and enforcement seem to be weak because of the vast territory, therefore we need an approach to effective management and efficient as well as small scale fisheries management by using the values of local wisdom in the District of Demta in Jayapura in Papua province.